2018
DOI: 10.1080/09583157.2018.1461197
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Pakistani isolate SpltNPV-Pak-BNG in second, third and fourth instar larvae of the leafwormSpodoptera litura

Abstract: Recently, a novel isolate of the baculovirus Spodoptera litura nucleopolyhedrovirus (SpltNPV) has been isolated from Pakistan, which is distinct from the type species SpltNPV-G2 (ICTV). Here, we examined the biological activity of this isolate (SpltNPV-Pak-BNG) in second (L2), third (L3) and fourth instar (L4) larvae of the leafworm S. litura, more specifically to measure biological properties that are relevant for use of this virus for pest control under field conditions. The median lethal dose for L2 and L3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The enhanced effect of tannic acid on the toxicity of chlorantraniliprole against third-stage instar was evaluated using diet incorporation method for the bioassay [38]. This developmental stage was selected because second and third instars have been identified as the target stage for optimal insect pest management [39]). The stock solution of chloranraniliprole (2.5 mg/L in distilled water) was diluted using 0.1% (w/v) 'Triton X-100' aqueous solution and the final concentration of 2 mg/g tannic acid mixed into the semi-synthetic diet.…”
Section: Enhanced Effects Of Tannic Acid With Of Chlorantraniliprole mentioning
confidence: 99%
“…The enhanced effect of tannic acid on the toxicity of chlorantraniliprole against third-stage instar was evaluated using diet incorporation method for the bioassay [38]. This developmental stage was selected because second and third instars have been identified as the target stage for optimal insect pest management [39]). The stock solution of chloranraniliprole (2.5 mg/L in distilled water) was diluted using 0.1% (w/v) 'Triton X-100' aqueous solution and the final concentration of 2 mg/g tannic acid mixed into the semi-synthetic diet.…”
Section: Enhanced Effects Of Tannic Acid With Of Chlorantraniliprole mentioning
confidence: 99%
“…These genogroups strongly correlate to the regions where they were found and to a much lesser extent to the cropping system [5]. It was also found that four SpltNPV isolates, all originating from the Punjab, showed a faster speed-of-kill than the other SpltNPVs [5,10]. The close relatedness among the Pakistani SpltNPV isolates and their more distant relatedness to the SpltNPV-type species from China and SpltNPV isolates from Japan suggests that SpltNPV may have recently been introduced to Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we characterize the full-genomes of the SpltNPV-Pak-BNG and SpltNPV-Pak-TAX1 isolates, with low and high speed-of-kill respectively [5,10], using an NGS approach. RFLP analysis showed that these two isolates belong to different genogroups, with SpltNPV-Pak-BNG belonging to genogroup A and SpltNPV-Pak-TAX1 belonging to genogroup B [5].…”
Section: Introductionmentioning
confidence: 99%
“…Two viral stock concentrations, 3×10 6 and 3×10 7 OBs/ml, respectively, were prepared for conducting leaf disc bioassays. In each assay, 45 newly moulted 4 th instar larvae were individually placed in 24-well tissue culture plates (bottom diameter of 15.5 mm) to avoid cannibalism, and starved for 15 hr.…”
Section: Bioassaymentioning
confidence: 99%
“…A 3.33 µl volume of viral suspension was placed on each leaf disc and allowed to air-dry. Fifteen leaves were inoculated with the 3×10 6 OBs/ml solution, while fifteen other leaves were inoculated with the 3×10 7 OBs/ml solution. The 15 remaining leaves were mock inoculated with distilled water.…”
Section: Bioassaymentioning
confidence: 99%